Creating Positive Learning Environment in Primary School/Islamic Primary School Based on Integrative-Thematic Approach in Inclusion Class - Zidniyati . (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2013)
Learning environment becomes one of todays learningtools which has important role in reaching goals of learningprogram. The goals of national education in Indonesia isto create good generation who are smart and morallygood. In this paper, learning environment includesphysical and non-physical learning environment. The aimof this paper is to describe which learning environment issuitable for implementing the integrative-thematicapproach in inclusion class in Primary School/IslamicPrimary School. For this reason, there will be a discussionabout the theories of learning, they are behaviourism,cognitivism, and constructivism. Each of these theories oflearning has been responded in the creations of differentlearning environment.